Performing Shakespeare in Contemporary Japan: The Yamanote Jijosha’s The Tempest - Hamana, Emi (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
In considering the Yamanote Jijosha’s The Tempest, this paper explores the significance of performing Shakespeare in contemporary Japan. The company’s The Tempest reveals to contemporary Japanese audiences the ambiguity of Shakespeare’s text by experimenting with the postdramatic and a new acting style. While critically pursuing the meaning and possibility of theatre and performing arts today, this version of The Tempest powerfully presents a critical view of the blindness and dumbness of contemporary Japan, as well as the world represented in the play.